2020
DOI: 10.1016/j.neubiorev.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The medial prefrontal cortex - hippocampus circuit that integrates information of object, place and time to construct episodic memory in rodents: Behavioral, anatomical and neurochemical properties

Abstract: Rats and mice have been demonstrated to show episodic-like memory, a prototype of episodic memory, as defined by an integrated memory of the experience of an object or event, in a particular place and time. Such memory can be assessed via the use of spontaneous object exploration paradigms, variably designed to measure memory for object, place, temporal order and object-location inter-relationships. We review the methodological properties of these tests, the neurobiology about time and discuss the evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 447 publications
(538 reference statements)
3
69
0
1
Order By: Relevance
“…This potentially aligns with findings showing that women perform better than men in temporal ordering tasks and in estimating temporal features of remembered events ( 71 74 , 77 , 78 ). However, despite the robust evidence that supports superior performance of women in tests of episodic memory requiring recall of pictures and objects ( 79 , 127 ), no rodent studies to date– including the present, have identified corresponding significant or non-significant trends for female over male differences in rats' discriminations of “What.” While the presence or absence of sex differences could be related to the different cells and circuits that process what, where and when ELM domains [see ( 128 )], they may also be explained by the likelihood that discriminations based on multiple object features (“What”) are more easily made than those based on more constrained dimensions of “Where” or “When” ( 94 , 129 , 130 ). Accordingly, it may be necessary to increase the mnemonic demands of the WWWhen task (e.g., lengthen inter-trial intervals or reduce the number of distinguishing dimensions for sample objects) in order to reveal the full extent to which human patterns of domain-specific sex differences in episodic memory are recapitulated in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This potentially aligns with findings showing that women perform better than men in temporal ordering tasks and in estimating temporal features of remembered events ( 71 74 , 77 , 78 ). However, despite the robust evidence that supports superior performance of women in tests of episodic memory requiring recall of pictures and objects ( 79 , 127 ), no rodent studies to date– including the present, have identified corresponding significant or non-significant trends for female over male differences in rats' discriminations of “What.” While the presence or absence of sex differences could be related to the different cells and circuits that process what, where and when ELM domains [see ( 128 )], they may also be explained by the likelihood that discriminations based on multiple object features (“What”) are more easily made than those based on more constrained dimensions of “Where” or “When” ( 94 , 129 , 130 ). Accordingly, it may be necessary to increase the mnemonic demands of the WWWhen task (e.g., lengthen inter-trial intervals or reduce the number of distinguishing dimensions for sample objects) in order to reveal the full extent to which human patterns of domain-specific sex differences in episodic memory are recapitulated in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the hormone sensitivities of these important sites, circuits, and mnemonic processes, however, will require studies that not only combine hormone manipulations with site specific and disconnection lesion strategies but that also use an alternate version of the WWWhen task that incorporates recent and old familiar objects that are displaced into the test trial ( 173 ). Unlike the version of the WWWhen task used here, the test trial configuration of this task allows for explicit measurement of interactions between memory for object location and temporal ordering ( 128 ). While data from this lab have shown that hormone modulation of memory functions tapped in the version of the WWWhen task used here ( 64 ) differs from hormone sensitivities identified for memory processes engaged in preference tasks based on object features ( 174 ) or location ( 175 ) alone, testing on the alternative WWWhen task will be important in more definitively tying hormone impacts to the integrative aspects of ELM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that rats exhibit biased exploration, in terms of spending more time exploring the old familiar object (A1) than the old displaced object (A2) in the WWWhen/ELM protocol with a retention interval of 50 min (for a review, see Chao et al, 2020 ), we evaluated the exploration time of each object among the groups in the test trial, after a retention interval of 24 h. Multivariate ANOVA with exploration time for each object (A1, A2, B1, and B2) as the within-subject factor and groups as the between-subject factor revealed that there were no significant differences in exploration time of each object among the groups [ F ( 8 , 40 ) : 1.088; p = 0.391; η 2 = 0.179; Pillai’s trace = 0.358], which suggests that we can rule out effects such as a lack of drive to explore the objects or object preference throughout the test trial. In agreement, to evaluate the total exploration time of objects along experimental sessions, a repeated measure one-way ANOVA revealed session [ F ( 2 , 44 ) : 19.576; p < 0.001; η 2 = 0.471], group [ F (2, 22) : 3.748, p = 0.040, η 2 = 0.254], but not “group versus session” interaction effects [ F ( 4 , 44 ) : 1.368; p = 0.260, η 2 = 0.111].…”
Section: Resultsmentioning
confidence: 99%
“…Also, we evaluated the exploration patterns of A1 > B1 ( when : old familiar over old recent stationary objects), B2 > B1 ( where: novel location over old one in recent familiar objects) and A1 > A2 (old location over novel one in old familiar objects, that indicates an interaction between object-location and temporal-order in the WWWhen/ELM task and, hence episodic-like memory in animals) (for review Chao et al, 2020 ). Given that the exploration time of objects by groups alone did not meet normality, we conducted Wilcoxon signed-rank test with Bonferroni corrections to compare the exploration patterns.…”
Section: Resultsmentioning
confidence: 99%